Percutaneous management of paravalvular leak-related hemolytic anemia after transcatheter aortic valve replacement - Abiodun Idowu; Christian Witzke (European Journal of Case Reports in Internal Medicine)
We present a case of a patient with severe intravascular hemolytic anemia from a paravalvular leak after transcatheter aortic valve replacement and describe a technique of percutaneous repair of the leak with a vascular plug that resolved the patient’s transfusion-dependent hemolysis.